Numerical analysis and multi-objective optimization design of parabolic trough receiver with ribbed absorber tube - Peng Liu (Elsevier, 2021)
Parabolic trough collector (PTC) is the most cost-effective and mature concentrated solar power (CSP) technology for solar thermal utilization. However, the highly concentrated solar irradiation on the bottom of the absorber tube causes high local temperature, thermal stress and deformation, further leading to damage and performance degradation of PTC. In order to alleviate the above problem, a novel parabolic trough receiver (PTR) with ribbed absorber tube is proposed to improve the thermo-mechanical performance of PTC Moreover, the multi-objective optimization is employed to determine the optimal parameter combinations (slant angle (β), size (e), pitch (p), and number of the ribs (N)) of ribbed absorber tube coupled with 3D numerical simulation and the genetic algorithm (GA). Based on the TOPSIS method and performance evaluation criteria (PEC) value, the ribbed absorber tube with the optimal geometric parameters of β=15°, N=6, e=4.5mm and p=20mm is selected in the Pareto Front as the suggested optimal design. Furthermore, the performance of the PTRs at different inlet temperature of the fluid (Tin=400–600K), direct normal irradiance (DNI=300–1000 W/m2) and mass flow rate (M=0.62–3.72kg/s) are evaluated. It is found that the ribbed absorber tube can effectively disturb the fluid near the boundary and induce longitudinal vortexes flow, which results in significant improvement in heat transfer between fluid and absorber tube, thereby enhancing the performance of the PTC. Compared to the plain tube, the heat transfer and flow resistance of the optimal ribbed absorber are enhanced by 57%–225% and 222%–630%, and the heat loss is lessened by up to 79.3%, resulting in 2.3% and 2.2% improvement in the heat collecting efficiency and overall efficiency. The findings in this paper may provide practical guidelines for developing efficient PTC.